2000
DOI: 10.1111/j.1749-6632.2000.tb05200.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphorylation Cascades Associated with Methamphetamine‐induced Glial Activation

Abstract: Reactive gliosis is the most prominent response to diverse forms of central nervous system (CNS) injury. The signaling events that mediate this characteristic response to neural injury are under intense investigation. Several studies have demonstrated the activation of phosphoproteins within the mitogen-activated protein kinase (MAPK) and Janus kinase (JAK) pathways following neural insult. These signaling pathways may be involved or responsible for the glial response following injury, by virtue of their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
57
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 161 publications
(167 reference statements)
6
57
1
Order By: Relevance
“…These findings suggest an inflammatory response, or glial activation, because these metabolites are found in much higher concentrations in glial cells than in neurons (35), and are consistent with findings of acute methamphetamine-induced glial activation in rodents (36) and monkeys (37), as well as findings of chronic effects in monkeys up to 1.5 years after methamphetamine exposure (37). Methamphetamine, like HIV, has been reported to stimulate the production of the inflammatory cytokine, tumor necrosis factor α (38), and to increase binding and activation of the redox-responsive transcription factors, AP-1 and NF-kappaB (39).…”
Section: Discussionsupporting
confidence: 77%
“…These findings suggest an inflammatory response, or glial activation, because these metabolites are found in much higher concentrations in glial cells than in neurons (35), and are consistent with findings of acute methamphetamine-induced glial activation in rodents (36) and monkeys (37), as well as findings of chronic effects in monkeys up to 1.5 years after methamphetamine exposure (37). Methamphetamine, like HIV, has been reported to stimulate the production of the inflammatory cytokine, tumor necrosis factor α (38), and to increase binding and activation of the redox-responsive transcription factors, AP-1 and NF-kappaB (39).…”
Section: Discussionsupporting
confidence: 77%
“…This observation raises the possibility that stress induction of ATF3 may be mediated via activation of intracellular stress cascades as opposed to being mediated by increased dopaminergic transmission. Thus, although very high doses of methamphetamine can cause cell death via cellular stress pathways (Hebert and O'Callaghan, 2000;Jayanthi et al, 2004), there is no evidence that the amphetamine dose used in the present experiments activates cellular stress pathways. In contrast, ATF3 is known to be induced in non-nervous tissue by nonstress-related stimuli (Cho et al, 2001).…”
Section: Discussioncontrasting
confidence: 38%
“…It has been reported that treatment with METH at neurotoxic doses induces the robust phosphorylation of STAT3 in the mouse brain (Hebert and O'Callaghan, 2000). These findings raise the possibility that exposure to the drugs of abuse could produce the synaptic plasticity and/or neuronal toxicity via Jak/STAT pathway.…”
Section: Discussionmentioning
confidence: 90%